Flashcard Media as a Strategy to Strengthen Elementary Students’ Learning Interest: Flashcard sebagai Strategi untuk Meningkatkan Minat Belajar Siswa Sekolah Dasar - Rachwadi, Dhiyanissa Azzabila; Rezania, Vanda (Indonesian Journal of Education Methods Development, 2025)
Background: Learning interest is essential in elementary education, yet many students experience low engagement due to monotonous media and conventional teaching. Specific Background: Flashcards are visual tools that may improve attention, motivation, and learning involvement. Gap: Previous studies mostly focused on cognitive outcomes, while affective aspects such as learning interest remain understudied. Aim: This study investigates whether flashcard media strengthens learning interest among fourth-grade students. Methods: A quantitative experimental one-group pretest–posttest design was used involving 20 students. Data on learning interest were collected using a validated Likert-scale questionnaire and analyzed through normality testing and paired sample t-test. Results: The mean score increased from 88.80 (pretest) to 92.10 (posttest), with a significance value of 0.004, indicating a meaningful improvement after using flashcards. Novelty: This research highlights the role of flashcards not only in cognitive enhancement but specifically in supporting students’ affective engagement. Implications: Flashcards can be adopted as an accessible instructional tool to foster interest and increase engagement in elementary classrooms. Highlights:• Increased learning interest after flashcard implementation• Strengthened student engagement and participation• Practical use of visual media in elementary classrooms Keywords: Flashcard Media, Learning Interest, Elementary School, Visual Learning, Student Engagement